Prevalence of mastitis, antibiotic residues, and antibiotic resistant pathogens in dairy animals: Prevalence of mastitis in dairy animals - Kumar, Naresh; Dua, Kriti; Goel1, Prashant; Sandhu, Pooja; Jaswal, Avinash; Shekhawat, Anshul; Kalyan, Priya; Kaur, Gurjinder; Vishweswaraiah, Raghu (Indian Journal of Dairy Science, 2024)
The prevalence of mastitis in milking animals and subsequent antibiotic usage is one of the major concerns in dairy sector. In this work, a baseline data was generated by collecting 675 raw milk samples from organized and individual dairy farms in Haryana. The milk samples were screened for mastitis, antibiotic residues and antimicrobial resistance (AMR) E. coli and S. aureus using rapid BD Phoenix M50 ID/ AST system and conventional methods. The study indicated 14.37% animals infected with sub-clinical mastitis and 11.25% with clinical mastitis. 79 milk samples from normal and infected animals were found contaminated with antibiotic residues with presence of enrofloxacin, streptomycin, tetracycline, sulfa drugs and multi drug residues. Out of 675 samples, 173 were infected with mastitis with involvement of E. coli in 18.49% and S. aureus in 38.72%. In E. coli isolates, the maximum resistance of 25% was observed against Ampicillin, Ciprofloxacin and Levofloxacin and Extended spectrum β-Lactamase (ESBL) productionwas observed in 15.65% infected samples.The maximum resistance of 32% was observed in Staph. Aureus against Ampicillin and Penicillin-G and Methicilin Resistant Staph. aureus (MRSA) was found in 22.38% along with β-Lactamase resistance in 31.34% of  infected samples.The main reason behind the increasing number of resistant pathogens may be due to the indiscriminate use of antibiotics by untrained veterinary professionals and lack of diagnostic facilities, hence regular screening of sub-clinical mastitis should be practiced to control the usage of antimicrobials and resistant development in dairy pathogens.